Stroop event-related potentials as a bioelectrical correlate of frontal lobe dysfunction in multiple sclerosis. Issue 1 (December 2016) - Amato, N.; Cursi, M.; Rodegher, M.; Moiola, L.; Colombo, B.; Falautano, M.; Possa, F.; Comi, G.; Martinelli, V.; Leocani, L.
Abstract Background Dysfunction of higher cognitive abilities occurs in 40–60 % of people with multiple sclerosis (MS), as detected with neuropsychological testing, with predominant involvement of executive functions and processing speed. Event-related potentials to the Stroop are a bioelectrical correlate of executive function. We tested whether event-related potentials to the executive Stroop test may reflect executive dysfunction in MS. Methods 29 MS patients (M/F:14/15; mean age 40 ± 8), and 16 healthy control subjects were included in the study (M/F:7/9; mean age 36 ± 10). Patients underwent a neuropsychological battery and, according to the performance obtained, they were divided in two groups: 13 frontal patients (F-MS; M/F:6/7; mean age: 40 ± 8) and 16 non frontal patients (NF-MS; M/F:8/8; mean age: 41 ± 7). Simple and complex reaction times to the Stroop task were measured using a computerized system. Event-Related Potentials (ERPs) to the same stimuli were obtained from 29 channel EEG, during mental discrimination between congruent and incongruent stimuli. Multivariate analysis was performed on reaction times (RTs) and ERPs latencies; topographic differences were searched with low resolution brain electromagnetic tomography (LORETA). Results Significant group effects were found on the percentage of correct responses: F-MS subjects committed more errors than the other two groups. F-MS patients showed delayed P3 and N4 compared to NF-MS patients and delayed P2, N2, P3 and N4 compared to controls. NF-MS subjects showed significantly slower P2, N2 and P3 compared to control subjects. Moreover, frontal score correlated negatively with ERPs' latency and with complex RTs. At source analysis F-MS patients presented significantly reduced activation predominantly over frontal, cingulate and parietal regions. Conclusions Taken together, these findings suggest that bioelectrical activity to the Stroop test may well reflect the speed and extent of neural synchronization of frontal circuits. Further studies are needed to evaluate the usefulness of Stroop reaction times and ERPs for detecting frontal involvement early at a subclinical stage, allowing early cognitive therapy, and as a paraclinical marker for monitoring treatment outcomes.